Report of the expert consultation on the assessment of socio-economic impacts of Aquaculture : (Food and Agriculture Organization of the United Nations, 2008)
This report identifies the many positive and negative impacts of aquaculture with their far-reaching socio-economic implications. While they agreed that multi-criteria decision-making framework using analytical hierarchy process as a measurement technique is a suitable method for assessing socio-economic impacts of aquaculture, experts recognized that other methods such as the costs benefits analysis could also be used depending on circumstances.